Mentalization-based treatment for adolescents with conduct disorder (MBT-CD): a feasibility study - Hauschild, Sophie; Kasper, Lea A.; Volkert, Jana; Sobanski, Esther; Taubner, Svenja (European child & adolescent psychiatry, 2023)
Conduct disorder (CD) is a common psychiatric disorder in youth characterized by persisting norm-violating or aggressive behavior. Considering high individual and societal burden, feasible and effective psychotherapeutic treatment is desirable. Yet, treatments and research in this patient group are scarce. This study investigates the feasibility of mentalization-based treatment for adolescents with CD (MBT-CD) in terms of acceptability of MBT-CD and scientific assessments by participants as well as necessary organizational resources to conduct a consecutive randomized controlled trial (RCT). Recruitment, adherence and treatment session numbers were descriptively analyzed. Treatment evaluation interviews were qualitatively analyzed. A subset of sessions of therapists without prior MBT experience was rated for MBT adherence. Quantitative data were used to plan a consecutive RCT. Pre to post treatment changes in diagnosis and self-reported aggression, mentalizing and personality functioning were preliminarily analyzed. N = 45 adolescents with CD were recruited. 43% dropped out. Acceptance of scientific assessments was somewhat lower than therapy adherence (questionnaires filled out by ~ 80% of adolescents in treatment), and low at follow-up (25% of treatment completers). Mean session number was 30.3. Most treatment completers were satisfied with MBT-CD. Referrals mainly came from child and youth services and psychiatry. Nine of 16 sessions rated for MBT adherence were adherent. A priori sample size estimation for a prospective RCT with a drop-out rate of 43% yielded a sample of N = 158 to detect an effect f = .15 with 80% power in a repeated measures ANOVA. Pre-post analyses revealed diagnostic improvement in 68%. Of self-reported data, empathy pathology improved. Findings provide a sound basis for a consecutive feasibility and pilot RCT.